Strengthening the Sharia Economy for the Indonesian Diaspora in Malaysia through the Strategic Collaboration of PARI, ASEANACA, and MIMTC in the Nusantara Trade Exploration Program - M Djidin; Meilia Risna; Umi Khulsum; Pertiwi Utami; Tejo Waskito; Ghasem Muhammadi; Ashabinur Adam Maulana; Abdul Aziz (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2026)
This international Community Service (PKM) program aims to strengthen the sharia economic capacity of the Indonesian diaspora in Malaysia, particularly those affiliated with the Persatuan Anak Rantau Indonesia (PARI) in Selangor. The program was carried out under the 2026 Archipelago Trade Exploration framework through a strategic collaboration among the ASEANACA Academic Association, the Malaysia International Marketing & Trade Chamber (MIMTC), and PARI. The approach is grounded in participatory empowerment, emphasizing sharia economic literacy, business network development, and cross-border partnership facilitation oriented toward long-term sustainability. Beyond strengthening participants' understanding of Islamic economic principles, the program actively promotes sharia values, sound business governance, and international market access. A key outcome is the signing of a Memorandum of Understanding (MoU) among PARI, ASEANACA, and MIMTC Malaysia as a formal foundation for sustained cooperation in trade, entrepreneurship, and diaspora-based Islamic economic advancement. This program is expected to raise the economic competitiveness of the Indonesian diaspora while reinforcing Islamic economics as a normative and strategic framework for building a sustainable, inclusive, and mutually beneficial business ecosystem.